2013
DOI: 10.1111/jir.12023
|View full text |Cite
|
Sign up to set email alerts
|

Respecting autonomy in the end‐of‐life care of people with intellectual disabilities: a qualitative multiple‐case study

Abstract: If caregivers and relatives embrace autonomy as a relational construct, attained through an open, active and reflective attitude, and have more access to knowledge about communication and how to identify end-of-life care needs, this could lead to improved respect for the ID persons' autonomy at the end of life. We discuss the view that a relational concept of autonomy is useful for describing respect for autonomy in end-of-life care for people with ID, but that more reflection and openness is needed to suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 29 publications
2
54
0
2
Order By: Relevance
“…If caregivers feel ill equipped to do this work, find it personally distressing, or experience other negative consequences, then they will often avoid issues of dying and death. Disability staff reported that they did not know how to inform people with intellectual disability about dying and death (Bekkema et al, 2014;Wiese et al, 2013). Clearly, one solution to this situation is training caregivers about how to do so effectively.…”
Section: Time For Actionmentioning
confidence: 98%
See 1 more Smart Citation
“…If caregivers feel ill equipped to do this work, find it personally distressing, or experience other negative consequences, then they will often avoid issues of dying and death. Disability staff reported that they did not know how to inform people with intellectual disability about dying and death (Bekkema et al, 2014;Wiese et al, 2013). Clearly, one solution to this situation is training caregivers about how to do so effectively.…”
Section: Time For Actionmentioning
confidence: 98%
“…There is also some evidence to suggest that caregivers avoid the topic, either to protect themselves from possible distress, or because they do not know how to broach the issue (Wiese et al, 2013). Talking about the end of life is undeniably difficult, and combined with the learning difficulties experienced by many people with intellectual disability, multiple challenges exist (Bekkema, de Veer, Hertogh, & Francke, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…; Bekkema et al . ,b). The reasons for the lack of involvement include but are not limited to communication challenges, lack of education on caring for individuals with an intellectual disability by the medical community, incorrect assumptions that the individual lacks capacity to consent, and fear of legal consequences if formal caregivers are accused of not providing enough care (Ellison & Rosielle ; Johnson ; Lotan & Ells ; Friedman et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Bekkema et al . ,b). Medical staff and other members of the multidisciplinary team may be vulnerable to assumptions that the individual with an intellectual disability does not possess the capacity to understand the terminal diagnosis and therefore is unable to consent to treatment (Johnson ; Huneke et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation